Bottom-up synthesis of WS2 nanosheets with synchronous surface modification for imaging guided tumor regression. (August 2017) - Wang, Shige; Zhao, Jiulong; Yang, Hailun; Wu, Chenyao; Hu, Fei; Chang, Haizhou; Li, Guixiang; Ma, Dan; Zou, Duowu; Huang, Mingxian
Graphical abstract: Abstract: Two-dimensional transition metal dichalcogenides (TMDs) have been receiving great attention as NIR photothermal transducing agent in tumor photothermal therapy. Keeping in mind the low efficiency of the conventional top-down exfoliated 2D TMDs and the complexity of their surface modifications, we herein proposed a bottom-up strategy for the one-pot hydrothermal and controlled synthesis of surface polyvinyl pyrrolidone (PVP) modified WS2 nanosheets. The material design was based on the chelating-coordinating effect between the lone pair electrons of oxygen of PVP carbonyl group and the unoccupied orbital (5d orbitals) of tungsten. The WS2 nanosheets with synchronous surface PVP grafting showed an excellent photothermal conversion performance, while the surface anchored PVP guaranteed its colloidal stability. Moreover, the strong X-ray attenuation ability and near-infrared (NIR) absorbance of WS2 -PVP360kDa enabled the sensitive in vitro and in vivo computed tomography and photoacoustic imaging. The WS2 -PVP360kDa nanosheets were biocompatible and exhibited promising in vitro and in vivo anti -cancer efficacy. Findings in this report may greatly promote the design of colloidal stable and biocompatible 2D TMDs and their future clinical translations. Statement of Significance: A bottom-up strategy for the one-pot and controlled synthesis of surface polyvinyl pyrrolidone (PVP) modified WS2 nanosheets was proposed for the first time. By hydrothermally treating the mixture solution of tetrathiotungstate and PVP, Owing to the chelating-coordinating effect between the lone pair electrons of oxygen of PVP carbonyl group and the unoccupied orbital (5d orbitals) of tungsten, PVP was synchronously graphed on WS2 -PVP nanosheets surface. The formed WS2 -PVP nanosheets were colloidal stable, biocompatible, and exhibited promising computed tomography, photoacoustic imaging and tumor photothermal therapy efficacy both in vitro and in vivo .